Sri Lanka Development Update 2021 : Economic and Poverty Impact of COVID-19 - World Bank (World Bank, Washington, DC, 2021)
Amid the Coronavirus (COVID-19) pandemic, Sri Lanka’s economy contracted by 3.6 percent in 2020, the worst growth performance on record, as is the case in many countries fighting the pandemic. Swift measures enacted by the government in the second quarter helped contain the first wave of Coronavirus (COVID-19) successfully, but these measures hit sectors like tourism, construction, and transport especially hard, while collapsing global demand impacted the textile industry. Job and earning losses disrupted private consumption and uncertainty impeded investment. As a result, the economy contracted by 16.4 percent (y-o-y) in the second quarter. The economy began to recover in the third quarter as the first wave was brought under control and containment measures were relaxed. The momentum continued in the fourth quarter as the economy was broadly kept open despite a second wave of Coronavirus (COVID-19) infections. The special focus section of this edition discusses the impact of Coronavirus (COVID-19) on poverty in Sri Lanka as of 2021.